Ehrlichia Isolate from a Minnesota Tick: Characterization and Genetic Transformation - Lynn, Geoffrey E. (Appl Environ Microbiol, 2019)
Ehrlichia muris subsp. eauclairensis is recognized as the etiological agent of human ehrlichiosis in Minnesota and Wisconsin. We describe the culture isolation of this organism from a field-collected tick and detail its relationship to other species of Ehrlichia. The isolate could be grown in a variety of cultured cell lines and was effectively transmitted between Ixodes scapularis ticks and rodents, with PCR and microscopy demonstrating a broad pattern of dissemination in arthropod and mammalian tissues. Conversely, Amblyomma americanum ticks were not susceptible to infection by the Ehrlichia. Histologic sections further revealed that the wild-type isolate was highly virulent for mice and hamsters, causing severe systemic disease that was frequently lethal. A Himar1 transposase system was used to create mCherry- and mKate-expressing EmCRT mutants, which retained the ability to infect rodents and ticks. IMPORTANCE Ehrlichioses are zoonotic diseases caused by intracellular bacteria that are transmitted by ixodid ticks. Here we report the culture isolation of bacteria which are closely related to, or the same as the Ehrlichia muris subsp. eauclairensis, a recently recognized human pathogen. EmCRT, obtained from a tick removed from deer at Camp Ripley, MN, is the second isolate of this subspecies described and is distinctive in that it was cultured directly from a field-collected tick. The isolate’s cellular tropism, pathogenic changes caused in rodent tissues, and tick transmission to and from rodents are detailed in this study. We also describe the genetic mutants created from the EmCRT isolate, which are valuable tools for the further study of this intracellular pathogen.